2021
DOI: 10.1186/s13014-021-01759-9
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy versus observation following gross total resection for atypical meningioma: a systematic review and meta-analysis

Abstract: Background The impact of adjuvant radiotherapy (RT) on atypical meningioma (AM) underwent a gross total resection (GTR) remains unclear, showing conflicting results from various studies. The objective of this study was to perform an updated meta-analysis for observational studies to determine the effect of adjuvant RT after GTR on local recurrence and survival outcomes compared to observation after GTR. Methods PubMed, Embase, and Web of Science we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
(16 reference statements)
0
22
0
Order By: Relevance
“…Song et al [ 33 ] accumulated 24 studies reporting on 3078 patients with WHO grade 2 meningioma, finding that post-operative radiotherapy improved progression free survival regardless of resection extent with a pooled hazard ratio of 0.41 (95% confidence interval 0.30–0.55) after subtotal resection, and 0.73 (95% confidence interval 0.52–0.92) after gross total resection. Similarly, Chun et al [ 34 ] identified 25 studies reporting outcomes of WHO grade 2 meningiomas following gross total resection, comprised of 1232 patients not receiving postoperative radiotherapy and 384 patients receiving postoperative radiation. Again, postoperative radiotherapy improved local recurrence and progression free survival, with pooled hazard ratios of 0.50 (95% confidence interval 0.36–0.68) and 0.66 (95% confidence interval 0.51–0.84), respectively.…”
Section: Efficacy and Safety Of Radiotherapy For Meningiomamentioning
confidence: 99%
“…Song et al [ 33 ] accumulated 24 studies reporting on 3078 patients with WHO grade 2 meningioma, finding that post-operative radiotherapy improved progression free survival regardless of resection extent with a pooled hazard ratio of 0.41 (95% confidence interval 0.30–0.55) after subtotal resection, and 0.73 (95% confidence interval 0.52–0.92) after gross total resection. Similarly, Chun et al [ 34 ] identified 25 studies reporting outcomes of WHO grade 2 meningiomas following gross total resection, comprised of 1232 patients not receiving postoperative radiotherapy and 384 patients receiving postoperative radiation. Again, postoperative radiotherapy improved local recurrence and progression free survival, with pooled hazard ratios of 0.50 (95% confidence interval 0.36–0.68) and 0.66 (95% confidence interval 0.51–0.84), respectively.…”
Section: Efficacy and Safety Of Radiotherapy For Meningiomamentioning
confidence: 99%
“…In contrast, patients in our cohort did not receive routine RT after surgery for a grade 2 or 3 meningioma. Time to recurrence was shorter and tumor control worse in our patients than in patients who received RT after surgery in the published literature [ 38 , 39 ]. However, long-term follow-ups typically show that meningiomas recur despite RT, indicating that the benefit is the delay of recurrence rather than the cure.…”
Section: Part 1 Long-term Follow-up and Outcomementioning
confidence: 82%
“…SRS is typically recommended for small residual or recurrent tumors [ 24 ]. Several studies have shown that RT improves PFS but not OS [ 38 , 39 ]. Rogers et al [ 12 ] reported a 59% 3-year PFS and 69% local control after RT for high-risk meningiomas, indicating that RT may be beneficial in these patients.…”
Section: Part 1 Long-term Follow-up and Outcomementioning
confidence: 99%
“…This may be secondary to the heterogeneity in the indications for ART across institutions and selection bias, given that our ART group exhibited more unfavorable characteristics such as a larger tumor size, lesser GTR, and higher Ki-67. However, a recent meta-analysis of retrospective studies observed that ART significantly increases PFS after GTR of atypical meningiomas (30). Table 3 shows the results of retrospective series comparing ART and surveillance and the results of prospective non-randomized studies.…”
Section: Discussionmentioning
confidence: 99%